Art And Culture Online Learning Of Sub-Material Music In SMP Negeri 1 Bawang Banjarnegara (Jurnal Seni Musik, 2022)
Online learning activities in junior high schools are a method of carrying out teaching and learning activities on the subject of music in the midst of the Covid-19 pandemic situation. The formulation of the problem in this study is to determine the barriers to learning the art of music online in Class IX E in SMP Negeri 1 Bawang. The purpose of this study was to determine, describe, and analyze online music learning in SMP N 1 Bawang. This research uses a qualitative research method of case study with a musicology and pedagogic approach. Data were collected through observation, interviews, and documentation. Data validity techniques using triangulation of data sources. Data were analyzed by stages of data collection, data reduction, data presentation, and conclusion. The results showed that online teaching and learning activities on the subject of music in SMP Negeri 1 Bawang there are three stages of learning activities, namely opening activities, main activities, and closing activities. The types of learning used during online learning are synchronous, asynchronous, and blended learning. These three types of learning equally divide students into several study groups to make it easier and more effective in delivering material by online.